Double resonance spectroscopy reveals structure and dynamics near transition states - Joshua H. Baraban; Robert W. Field (Nature Communications)
A shared ambition of molecular spectroscopy and molecular dynamics is to establish the truths of chemical intuition on solid physical bedrock. Experimental characterization of the transition state was thought unattainable, but modern techniques have begun to achieve the incredible.